Improvement of accuracy and diagnostic significance of breast tumor fine-needle aspiration biopsy by miRNA analysis of material isolated from cytological smears - N. N. Kolesnikov; S. E. Titov; Yu. A. Veryaskina; A. V. Vladimirova; R. B. Samsonov; A. S. Artem’eva; V. I. Novik; L. M. Bershteyn; I. F. Zhimulev; A. V. Malek (Успехи молекулярной онкологии)
Relevance. Breast cancer is the most commonly diagnosed cancer in women. Tumor biopsy, a key diagnostic approach, is required to evaluate the nature of tumor and to determine the therapeutic strategy. In clinical practice methods are being applied: trepan-biopsy and fine needle aspiration biopsy (FNAB). The latter is less traumatic however is used less often because it provides with less information. Moreover, dependence from quality of biopsy and qualification of morphologist are attributes of both techniques. A possibility to use biopsy material for farther analysis of tumor-markers would open a perspective to obtain more information and to improve objectivity of traditional diagnostic approaches, including FNAB. MicroRNAs (miRNAs), regulatory molecules involved in control of virtually all physiologic and pathologic process, emerged as promising tumor markers. Malignant transformation of mammary gland epithelia is associated with specific alterations of cellular miRNAs profile. Analysis of these alterations is of great diagnostic potency.Objective. Development of method for miRNAs analysis in cytological smears material and evaluation of its practical applicability.Material and methods. Archived cytological material (smears on the glass slides) from patients with benign tumor and breast cancer was used. Analysis of miRNAs expression was performed by reverse transcription followed by quantitative PCR. Results of reverse transcription polymerase chain reaction were analyzed with use of relevant cytological and morphological data.Results. Method of miRNAs analysis in material of cytological smears was developed. Expression of 9 miRNAs in 80 samples was evaluated. Statistically significant expression difference between benign and malignant tumor samples was found for 5 miRNAs: miR-21, miR-205, miR-125b, miR-200a, miR-221. MiR-125b exhibited most prominent expression dysregulation: malignant transformation of mammary epithelium is associated with 500 fold decrease of miR-125b expression level. Expression alterations of several miRNAs were revealed to correlate with clinically relevant characteristics of tumors.Conclusions. Results of our study indicated the possibility of miRNAs expression analysis in the FNAB material and the applicability of this method as additive approach to the convention cytological examination. Application of this method will allow to specify diagnosis and to optimize choice of the therapeutic strategy.